Building Business Models with Blocks In Chain: Business Models in a Blockchain Environment - Stošić Panić, Danijela; Vučurović, Anđelija (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Disruptive technologies of the Industry 4.0 are not only disrupting the technological field, but they are also changing the competitive environment and the sources of business competitiveness. Although the business potential of blockchain seems to be promising, the existing research on blockchain technology are in most cases focused on the technical aspects. Therefore, the aim of the paper is to explore the possibilities for wider business use of blockchain technology (apart from its implementation within the financial services context) and to map its effects on the existing business models. Moreover, the paper is dealing with blockchain-inspired digital business models in an attempt to identify the main directions of new, blockchain-based business models development. As usual for the first stages in the development of a certain research area, the paper is exploratory. Moreover, it is theoretically oriented and it presents the results of relevant literature research. As a conceptual paper, it is built around the concept of the business model and the blockchain potential to affect its functioning and dynamics. The theoretical research presented by the paper reveals that blockchain technology has the potential to affect all the elements of the existing business models, but also to inspire the development of entirely new digital business models.